Uterus’ cancer prevention: women’s perceptions to their first examination and the professional performance - Sousa, Ivna Giovana da Silva; Moura, Escolástica Rejane Ferreira; Oliveira, Nancy Costa de; Eduardo, Kilvia Gardênia Torres (Rev Rene, 2008)
The aim of the study was to survey about women’s feelings concerning the first examination for cancer prevention and to identify favorable professional attitudes for the well being of the women during the examination. It was an exploratory-descriptive study which took place at the Instituto de Prevenção do Câncer do Ceará, with 34 women from March to April 2006. All of them fit into the criteria of having been examined for the first time and accepted to take part in this study. The data were collected through interviews. Along with them there were the five professionals responsible for the examination. The organization of their speech was according to Bardin’s Categorical Analysis Technique of Content Analysis. The women’s feeling, were grouped in the following categories: shame, fear, tension, discomfort and pain, laboratory body, and naturalness. The attitude of the professional included: dialog, touch, patience, welcoming and getting closer to the women’s cultural universe. The attitudes mentioned by the professionals were effective and can be used as suggestions for the professionals of the area